Comparative review of large animal models for suitability of proximal aortic endovascular repair - Abhishekh Srinivas; Ming Yii; Julian A. Smith (University Library System, University of Pittsburgh, 2022)
Background The advent of TEVAR heralds a paradigm shift in treating descending aortopathies and is viewed as a potential option for ascending aortic dissection (AD) repair too. Currently, TEVAR's usage for ascending aortopathies remains limited. Consequently, an urgent requirement exists to choose appropriate animal models to better contemporary understanding of endovascularly treating Type-A ADs. This review article provides a summary of current literature on this topic. Two broad sections are covered, including the macroscopic differences between adult swine, ovine and porcine species versus that of their human counterparts, as well as the valvular, aortic and coronary vasculature variances.   Methods A narrative review was conducted to integrate current findings of anatomical differences in valvular and ascending aortic anatomy amongst the aforementioned species. An electronic search of PubMed and Ovid Medline databases from January 1965 to June 2020 was performed, limited to articles published in English.    Results Whilst macroscopic anatomy remains grossly similar, differences in valvular leaflet shape are present, with swine and porcine models possessing anatomic characteristics that are comparable to their human counterparts. Research into inter-species ascending aortic anatomy has not been extensively performed, highlighting a literature gap. Conversely, multiple morphological studies have highlighted that swine coronary vasculature is closely resemblant to that of man.   Conclusion Both swine and ovine species are suitable as appropriate animal models in examining the feasibility of endovascular stent-grafts for ascending ADs. However, given the similarities in coronary and aortic valve anatomy to their human analogues, porcine models are better suited for this purpose.